Dampak Pengembangan Objek Wisata Tanjung Bias Terhadap Kesejahteraan Masyarakat di Wilayah Pantai Tanjung Bias, Kecamatan Batu Layar, Kabupaten Lombok Barat - Maulana Muhammad Firdaus; Iwan Harsono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Tanjung Bias Beach, located in West Lombok Regency, West Nusa Tenggara Province, represents a promising coastal tourism destination characterized by its natural allure, including stunning sunset vistas, expansive shorelines, and the seamless integration of local microenterprises such as food stalls, cafes, entertainment services (e.g., horse rentals and photography), and small-to-medium enterprises (SMEs) specializing in souvenirs. This study aims to examine the developmental potential of tourism in the area, its implications for community welfare, and synergistic initiatives among stakeholders to ensure long-term sustainability. The findings reveal that tourism at Tanjung Bias has significantly boosted local incomes and employment opportunities, facilitated by active community involvement through the Village-Owned Enterprise (BUMDes) of Senteluk Village in managing facilities (e.g., restrooms, parking, and photo spots) and collecting a 10% levy. Development efforts encompass digital promotion campaigns led by provincial and regency governments, training programs on social media content creation, and private-sector collaborations (e.g., Pelindo Peduli) focused on infrastructure enhancements and financial literacy initiatives commencing in 2024. Nevertheless, key challenges persist, including deteriorated road infrastructure, limited promotional outreach, initial community resistance, human resource constraints (particularly in foreign language proficiency and service delivery), and environmental repercussions such as heightened waste accumulation. While positive economic outcomes—such as augmented regional fiscal revenues and the emergence of tourism-related professions—are evident, these are counterbalanced by social risks (e.g., cultural shifts) and environmental hazards (e.g., coastal degradation).